Productivity and heavy metal uptake in pearlmillet hybrids under treated sewage water application - Parveen Kumar; sandeep; pawan kumar; Rohtas kumar (Journal of Soil and Water Conservation, 2026)
The present study entitled “Performance of pearl millet (Pennisetum glaucum L.) hybrids to fertility levels under treated sewage water application”was conducted during Kharif 2021 and 2022. In the experiment two pearl millet hybrids viz. HHB 67 (Improved) and HHB 299 were taken along with five different fertility levelsviz. Control, 75 % RDN + FYM @ 5 t/ha, 75 % RDN + Vermicompost @ 2.5 t/ha, 75 % RDN + Vermicompost @ 2.5 t/ha + FYM @ 2.5 t/ha and 100 % RDN. The yield attributing characters and grain yield differed significantly between hybrids and among fertility levels. Between hybrids, HHB 299 recorded higher value of these attributes and yield over HHB 67 (Improved). Among fertility levels, application of 75 per cent RDN + vermicompost @2.5 t/ha + FYM @ 2.5 t/haresulted in higher yield and yield attributes during both years of study. Heavy metal content in both pearl millet grain and stover recorded lower in HHB 67 (Improved) over HHB 299 while integrated nutrient management practices resulted in lower heavy metal content in pearl millet grain and stover over 100 per cent RDN and control, among fertility levels.